Qualifying title statements of library catalogue of the university of Jaffna - Ketheeswaren, S.; Charles, E.Y.; Chandrasekar, K. (University of Jaffna, 2020)
Metadata is the primary element for bibliographic communications. Hence, metadata should be qualified for a fruitful exchange of knowledge. The study examines the statements of title-proper and other-title-information of the monograph catalogue maintained by the University of Jaffna for quality status. The statements of title proper and other-title-information have been taken from the same catalogue records for the study. Their quality status has been examined by comparing the respective statements maintained by the Library of Congress. The quality issues have been identified for the statements of the title-proper and the other-title-information, which have been contributed by leaving extra space, spelling mistake, typographical error, missing a part of the statement, missing a complete statement, the inclusion of extra part with the statement, and inclusion of complete extra statement. However, Typographical error and missing a complete statement are the most significant issues in qualifying title-proper and other-title-information, respectively. The catalogue records of the University of Jaffna do not have a substantial-quality issue for the bibliographic communication concerned through title-proper and other-title information statements. However, the statements of title-proper and other-title information of the University of Jaffna should be validated against qualifying the records to enhance bibliographic communication status.
Keywords: Cataloguing errors andcatalogue quality